Hubungan Antara Optimisme dengan Adversity Quotient Pada Siswa di SMP X: Correlation Between Optimism and Adversity Quotient for Students at SMP X - Masyitah Ilmi Budiarti; Dwi Nastiti (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Adversity Quotient reflects students’ capacity to cope with academic and psychosocial challenges during adolescence. Specific Background Junior high school students frequently encounter complex developmental demands that require psychological resilience, where optimism is assumed to play an important role. Knowledge Gap Empirical evidence on the relationship between optimism and adversity quotient among Indonesian junior high students remains limited, particularly within evolving educational contexts. Aims This study aimed to examine the correlation between optimism and adversity quotient among students at SMP X. Using a quantitative correlational design, data were collected from 132 students selected through stratified random sampling. Results Pearson correlation analysis revealed a significant positive relationship between optimism and adversity quotient (r = 0.385, p < 0.05), indicating that higher optimism is associated with stronger adversity quotient. Most students were categorized at moderate levels of both variables. Novelty This research provides updated empirical findings within a contemporary junior high school setting, considering current student characteristics and contextual dynamics. Implications The findings suggest that strengthening students’ optimism may support their capacity to face academic difficulties, encouraging schools to implement psychoeducational programs and collaborative support involving teachers and parents to foster psychological resilience Keywords: Adversity Quotient, Optimism, Junior High Students, Psychological Resilience, Educational Psychology Key Findings Highlights: Optimism shows a significant positive association with students’ adversity quotient. Most participants demonstrate moderate levels of both psychological variables. Optimistic perspectives are linked with stronger coping capacity in academic contexts.